Of rice and men: climate change, religion, and personhood among the Diola of Guinea-Bissau - Davidson, Joanna (Journal for the Study of Religion, Nature and Culture, 2012)
When Diola Christians participated in their male initiation rites despite missionary objections, the argument was framed in theological terms. But Diola actions regarding this and other religious practices can only be understood within the wider frame of ecological changes that have challenged not only their agrarian livelihoods but their very conceptions of personhood and processes of socialization. Given the decline in rain, Diola males can no longer ‘become men’ in the rice paddies. By drawing out connections among Diola agrarian culture, ideals of masculinity, current environmental conditions, and missionary pressures, I argue that this incident—and, by implication, religious change more broadly—must be appreciated not only for its theological signi?cance within Diola agrarian culture, but as enmeshed in contemporary dynamics of climate change.
free
Keywords: Africa.; Agriculture; Agriculture – Religious aspects; Catholic Church – Controversies; Catholic Church – Guinea-Bissau; Catholics; Christianity and African religions; Climatic changes; Cosmology; African; Diola (African people); Droughts; Guinea-Bissau.; Initiation rites; Masculinity; Men – Religious life; Rice – Religious aspects; Sex role